2012
DOI: 10.1155/2012/751686
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Nanoparticles Interactions with Plants: Morphological, Physiological, and Genotoxic Aspects

Abstract: Nanoparticles (NPs) are characterized by their small size (less than 100 nm) and large surface area, which confer specific physicochemical properties as strength, electrical, and optical features. NPs can be derived from natural or anthropic sources, such as engineered or unwanted/incidental NPs. The composition, dimension, and morphology of engineered NPs enable their use in a variety of areas, such as electronic, biomedical, pharmaceutical, cosmetic, energy, environmental, catalysis, and materials sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 69 publications
1
54
0
1
Order By: Relevance
“…Diverse results have been achieved; positive effects on plant growth were reached only at low concentrations (Diatloff et al, 2008) while toxicity was shown at higher concentrations (LopezMoreno et al, 2010b). Furthermore, several studies demonstrated that nanoparticles can also have no significant or even positive effects on plants (Remedios et al, 2012). However, all these studies analyze the effects of nanoceria in seed plants and fewer have focused on algae (Rodea-Palomares et al, 2011;RodeaPalomares et al, 2012).…”
Section: Spore Germination and Exposurementioning
confidence: 99%
“…Diverse results have been achieved; positive effects on plant growth were reached only at low concentrations (Diatloff et al, 2008) while toxicity was shown at higher concentrations (LopezMoreno et al, 2010b). Furthermore, several studies demonstrated that nanoparticles can also have no significant or even positive effects on plants (Remedios et al, 2012). However, all these studies analyze the effects of nanoceria in seed plants and fewer have focused on algae (Rodea-Palomares et al, 2011;RodeaPalomares et al, 2012).…”
Section: Spore Germination and Exposurementioning
confidence: 99%
“…Sharma et al (2012) reported improvements in weight, root, shoot, vigor index, antioxidant activity, and reduction in malondialdehyde, and hydrogen peroxide levels when Brassica juncea seedlings were treated with AgNPs for seven days. These studies have shown that nanoparticles can boost antioxidant capacity of vegetables, but nanoparticles used in the previous studies were chemically synthesized and some have been found to be toxic to plant germination and growth (Remedios et al 2012;Narendhran et al 2016). Chemical method of synthesis is less eco-friendly and costly compared to biological (green) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In higher plants, different and conflicting effects of AgNPs have been reported, depending on the intrinsic AgNPs properties (size and shape, aggregation state, and surface coatings), experimental system, plant species and developmental stage (Remédios et al, 2012). Mahmoodzadeh et al (2013) reported that direct exposure to specific types of nanoparticles causes significant phytotoxicity, emphasizes the need for ecologically responsible disposal of wastes containing nanoparticles and also highlights the necessity for further study on the impacts of nanoparticles on agricultural and environmental systems.…”
Section: Introductionmentioning
confidence: 99%